Implementing Regulations for the Omnibus Law within the Taxation Cluster: A Delegated Legislation Perspective - Josua Marihot Armando Saragi; Fitriani Ahlan Sjarif; Maria Farida Indrati (Lex Publica, 2024)
This research explores the implications of Indonesia's Law Number 11 of 2020 concerning Job Creation, or the Omnibus Law, with a focus on delegated legislation and its role in fostering investment through regulatory clarity. The law emphasizes the importance of the timely implementation of regulations, mandating that all implementing regulations remain in effect unless they conflict with the new law. However, there is a gap in the existing literature regarding how delegated legislation influences the creation of these implementing regulations, particularly within the taxation cluster. Utilizing a qualitative design and normative juridical approach, the research analyzes the hierarchy of legal regulations in Indonesia, including the constitutional framework that supports economic growth. Data collection involves an in-depth examination of relevant laws and specific tax provisions introduced by Law 11/2020. The findings reveal that while the law aims for regulatory simplification, its implementation has led to over-regulation, complicating compliance for businesses. Recommendations include refining the preparation and organization of the law to enhance clarity and ensuring that the formation of delegated regulations aligns with established legislative principles. Ultimately, this research contributes to the discourse on regulatory reform, emphasizing the necessity for coherence and efficiency in Indonesia's legal landscape to promote a conducive environment for investment and economic development.